Can US monetary policy fall (again) into an expectation trap? - Roc Armenter; Martin Bodenstein (Federal Reserve Bank of New York, 2005)
We provide a tractable model to study monetary policy under discretion. We restrict our analysis to Markov equilibria. We find that for all parametrizations with an equilibrium inflation rate of about 2 percent, there is a second equilibrium with an inflation rate just above 10 percent. Thus, the model can simultaneously account for the low and high inflation episodes in the United States. We carefully characterize the set of Markov equilibria along the parameter space and find our results to be robust, suggesting that expectation traps are more than just a theoretical curiosity.
Keywords: E31; E52; E58; 330; expectation traps; monetary policy discretion; inflation; Geldpolitik; Diskretionäre Politik; Inflationserwartung; Inflationsrate; USA